Assessment of Slope Instability and Risk Analysis of Road Cut Slopes in Lashotor Pass, Iran. (10th April 2014) - Taherynia, Mohammad Hossein; Mohammadi, Mojtaba; Ajalloeian, Rasoul
Abstract : Assessment of the stability of natural and artificial rock slopes is an important topic in the rock mechanics sciences. One of the most widely used methods for this purpose is the classification of the slope rock mass. In the recent decades, several rock slope classification systems are presented by many researchers. Each one of these rock mass classification systems uses different parameters and rating systems. These differences are due to the diversity of affecting parameters and the degree of influence on the rock slope stability. Another important point in rock slope stability is appraisal hazard and risk analysis. In the risk analysis, the degree of danger of rock slope instability is determined. The Lashotor pass is located in the Shiraz-Isfahan highway in Iran. Field surveys indicate that there are high potentialities of instability in the road cut slopes of the Lashotor pass. In the current paper, the stability of the rock slopes in the Lashotor pass is studied comprehensively with different classification methods. For risk analyses, we estimated dangerous area by use of the RocFall software. Furthermore, the dangers of falling rocks for the vehicles passing the Lashotor pass are estimated according to rockfall hazard rating system.